Designing successful energy communities: A comparison of seven pilots in Europe applying the Multi-Actor Multi-Criteria Analysis. (August 2022) - Lode, Maria Luisa; Heuninckx, Shary; te Boveldt, Geert; Macharis, Cathy; Coosemans, Thierry
Abstract: Energy Communities (ECs) are emerging players in the energy market in the European Union. While policymakers promote their development by introducing legal entities for ECs, stakeholders experience various challenges during their set-up. A factor regarded key for the success of ECs is the consideration of stakeholder objectives. In this study we analysed seven case studies in Belgium, Spain, the Netherlands, and Greece, in which the multi-actor multi-criteria analysis (MAMCA) was applied in the design phase of ECs. We highlight commonalities and differences for each site, providing insight into the variations in EC options, stakeholders, as well as their preferences regarding the analysed ECs. We found that the aspects considered most important were emission reduction, community building, energy cost reduction and grid stability. EC options with greater end-consumer participation and shared benefits were preferred in all cases by all stakeholders. Highlights: Studies the design phase of Energy Communities (ECs) in four European Countries Data of applied Multi-Actor Multi-Criteria Analyses are the basis for comparison. Distribution system operators share similar criteria across the case studies. Citizens and energy cooperatives have a more diverse set of criteria. ECs with shared ownership and end-user participation were preferred.